ANTASEDEN DAN KONSEKUENSI PENGETAHUAN KOMPUTER DALAM MEMBENTUK NIAT PERILAKU MENGGUNAKAN SISTEM INFORMASI RUMAH SAKIT - Yuniena Jumpa Aneka Putri; Didik Setyawan; Finisha Mahaestri Noor (Jurnal Infokes, 2019)
This study aims to examine the intention to use an information system that is formed from behavioral intentions towards attitudes that are influenced by computer knowledge, computer anxiety, perceived ease of use, and social influence felt by employees in RSUD Dr. Moewardi Surakarta. The sampling technique is using purposive sampling with the population of employees in RSUD Dr.Moewardi Surakarta who are using information system counted 200 respondents. The hypothesis tested by using Structural Equation Modeling (SEM) using AMOS program. The results of this study indicate that attitudes positively influence employee behavioral intentions in using information system. All hypothesis supported, except H2, H5, and H6. This gives the meaning that the process of forming behavioral intentions uses information systems through attitudes formed by computer anxiety, computer knowledge, and perceived convenience that are influenced by the social environment.